2016
DOI: 10.1259/bjr.20160350
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric predictors of acute haematological toxicity in oesophageal cancer patients treated with neoadjuvant chemoradiotherapy

Abstract: Objective: Haematological toxicity (HT) is common in patients with oesophageal cancer (EC) treated with chemoradiotherapy (CRT). The Quantitative Analysis of Normal Tissue Effects in the Clinic guidelines provide no dose constraints for the bone marrow (BM) to avoid HT. We aimed to determine dosimetric factors associated with HT during CRT for EC. Methods: 41 patients with EC treated with neoadjuvant cisplatin and 5-fluorouracil-based CRT were retrospectively reviewed. Associations between the dose-volume hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(54 reference statements)
1
12
2
Order By: Relevance
“…This finding was consistent with previous studies, although the types of diseases and treatments differed (9,41,42). Chemotherapy and radiotherapy are both known to be myelosuppressive and could contribute to hematologic toxicity (43)(44)(45). Bone marrow-sparing radiotherapy could potentially reduce the incidence and severity of hematologic toxicities in patients with LACC (46).…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with previous studies, although the types of diseases and treatments differed (9,41,42). Chemotherapy and radiotherapy are both known to be myelosuppressive and could contribute to hematologic toxicity (43)(44)(45). Bone marrow-sparing radiotherapy could potentially reduce the incidence and severity of hematologic toxicities in patients with LACC (46).…”
Section: Discussionsupporting
confidence: 90%
“…The results when applying the TV dose–volume cutoff values to predict the risk of grade ≥3 leukopenia proposed by Lee et al (23) and Deek et al (22) are listed in Table 1 , including the number of patients (absolute and percentage of group) exceeding the threshold values for each treatment technique. The cutoff values proposed by Lee et al (23) and Deek et al (22) are different, but the trends observed were the same. The SFO62.5 and VMAT62.5bm plans showed the lowest risk of HT, which was greatly reduced compared with the 3D50, VMAT50, and standard VMAT62.5 plans.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted toxicity rates for the VMAT (10%-29%) and SFO62.5 (0%-10%) plans were much lower. However, the cutoff values from Lee et al (23) predicted a much lower incidence of grade >3 leukopenia for all treatment techniques, with a maximum of 14% of 3D50 patients predicted to experience HT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…National Comprehensive Cancer Network (NCCN) guidelines indicate that IMRT should only be administrated for unique clinical situation like reirradiation or inside clinical trials [9]. Limited data regarding BMS-RT are available for esophageal and gastric cancer [60,61]. Two main approaches for BMS-RT are: 1) dose reduction in total bone marrow (BMtot)-delineated as entire bone volume near planning target volume and 2) division of bone marrow on basis of functional imaging to red (active) bone marrow (BMact) and yellow (inactive) bone marrow (BMinact).…”
Section: Bone Marrow Sparing Rtmentioning
confidence: 99%